OPTIMASI VARIABEL YANG PALING BERPENGARUH PADA PEMBUATAN BIODIESEL DARI MINYAK BIJI RANDU DENGAN PROSES TRANSESTERIFIKASI - Mudzofar Sofyan; Ilham Tanjung; Herry Santosa (TEKNIK, 2014)
[Title: Biodiesel Production from Kapok Seed Oil with KOH Catalyst Using Two Steps Transesterification Process] Biodiesel is one of diesel fuel alternative made from renewable resources such as vegetable oils and animal fats. One of the natural ingredients that can be used as a material in the production of biodiesel is kapok seed. The existence of relatively abundant raw materials is a great opportunity to be developed into alternative energy options which developed on a commercial scale. Biodiesel from kapok seed oil can be made through a two-stage transesterification reaction which helped by using a base catalyst. This research aims to characterize the kapok seed oil, determine the most influential variables between temperature, the ratio of methanol-oil, and time against yield by the factorial design method, optimization variables that most influence on yield, and characterize the biodiesel. Two-stage transesterification process using KOH as the catalyst with changing variables: temperature, methanol-oil ratio, and time. The result showed that kapok seed oil has FFA content: 17.97% and a saponification number: 172.55 mgKOH/g. Most influential variable is the variable of time. At the variable optimization of time, the result were optimally obtained at the 105th minutes with yield: 77.39%. The characterization results of biodiesel’s product show from seven parameters of testing, four parameters are required in accordance with SNI.